Linking silvicultural aspects of pro-poor leasehold forestry for socio-economic benefits to the poor and vulnerable communities - Yadav, K. K.; Kafley, G. P.; Yadav, K. P. (Banko Janakari, 2018)
Government of Nepal has adopted different models like community forestry, leasehold forestry, collaborative forestry, buffer zone community forestry and public land agroforestry for management of forest resources. Poor focused leasehold forestry is only the approach adopted since early 1990 that has two major objectives: livelihood improvement and environmental conservation. Forest user groups of 5–15 households (HHs) are provided with part of national forests for a period of initial lease of 40 years. Leased forests are managed mainly with forestry crops, forage and non-timber forest products (NTFPs) to meet the dual objectives. Past studies and researches have indicated that leasehold forests are better than the hand over time however they are inadequate in dealing with silvicultural aspects in leasehold forestry (LF). This research paper has highlighted the significance of silvicultural aspects of leasehold forestry for overall socio-economic benefits to the poor and vulnerable forest users. Review of the existing policy and legal documents, studies and progress reports of the leasehold forestry projects implemented during the last two decades, consultation with leasehold forest user groups from five districts (Tehrathum, Makawanpur, Tanahun, Pyuthan and Doti) formed the main source of data for this article. Further, author’s own experiences in the sector were taken as supporting reliable information for the study. The study found that silvicultural practices, except plantations and weeding, were not adopted in leasehold forest but there was great potential for such practices to maximize the socio-economic benefits. Proper use of silvicultural practices might have increased contribution to currently realized benefits like (i) increased income of members i.e. poorest families (having less than 3 months secured foods) were reduced over years, (ii) group members had increased access to different networks and cooperatives, (iii) participation of women, poor and indigenous people increased in the decision-making process, and (iv) forest coverage was increased with respect to the hand over time. Some issues on silviculture aspects included proper guidelines for silvicultural methods, capacity of staff and leasehold forest user group members, smaller sizes of leasehold forests, and promotion of appropriate species. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 113-119